Discrimination Analysis of the Main Character in Movie Crazy Rich Asians - Jimmi Jimmi; Windi Mawadah (Pioneer: Journal of Language and Literature, 2021)
The objective of this research is to explain the types of discrimination shown by the main character in her society and to identify the effects that main character experienced after being discriminated. This research used descriptive qualitative method to analyze the movie. The subject of this paper was movie Crazy Rich Asians by Jon M Chu. The data analysis was conducted using U.S. Equal Employment Opportunity Commission theory reference. By the process of the analysis, it was that harassment, national origin discrimination, race/color discrimination, and religious discrimination were experienced by the main character. Not only that, the researchers found four types of effects experienced by a person after being discriminated, which are marginalization, disempowerment, low self-esteem and self-identity, and aggression or criminality.